Past and future responses of soil water to climate change in tropical and subtropical rainforest systems in South America - Márquez Arévalo, Santiago Maria (2023)
The Tropical Longleaf Forests Biome in South America (Biome 1 according to the WWF classification), composed mainly by the Amazon Rainforest and the Atlantic Forest, covers a representative portion of the planet's biodiversity. In the last decades (2001-2021) significant alterations in the use of the soil in this biome have been evidenced, threatening the future existence of the forests as known. From the evaluation of the variable Volumetric Soil Moisture (VSM), relating it with the hydric state, it was evaluated the state of the totality of the biome in the continent through maps and simulation with the Autoregressive Integrated Moving Average Model (ARIMA) making the forecast of the future climatic scenario based on the El Niño- Southern Oscillation (ENOS), meteorological systems. The use of Shared Socioeconomic Pathways (SSP) integrates the socio-political dynamics evident in the region to generate scientific advances in the search for effective strategies and actions for the monitoring and preservation of forests on the continent. A local scale analysis was also carried out for the Brazilian states of Acre and Rio de Janeiro. The results showed an increase in temperature and an increase in the amplitude of variation of precipitation in the biome. The use of ARIMA modeling showed changes up to 0.24 m3m-3 and increase in amplitude for future VSM values. Values were obtained in the range of (0.05 to 0.44 m3m-3), the December-January-February quarter (DJF) showed the highest average VSM value, while the June-July-August quarter (JJA) evidenced the lowest record. The lowest VSM records were in southern Amazonia (Ecuador, Peru, the Brazilian states of Acre, Mato Grosso, Pará and Maranhão) and in the Brazilian Atlantic Forest, the Southeast Region and the state of Bahia. Keywords: Biomes. Drought Vulnerability. Future simulation. ARIMA Analysis